EDUCATION INFORMATION SYSTEMS PLANNING PRACTICES AND PERFORMANCE OF GOVERNMENT AGENCIES IN MALAYSIA - Hisyam Harun; Mohd Khairuddin Hashim; Abdul Rahmat (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2018)
The relevance and applicability of Strategic information systems planning (SISP) to both private and public organizations have been emphasized in the literature. However, the literature review indicates that not many studies have attempted to examine the relationships between SISP practices and performance of organizations in the public sector. In an attempt to address this issue, this study examined the relationships between SISP practices and performance of government agencies. The data for the study was data gathered from 54 government agencies in Malaysia that adopted the SISP. Based on the analysis of the data collected from the government agencies, the results of the study indicated significant positive relationships between SISP practices and performance of the agencies.